Survivin and Related Proteins in Canine Mammary Tumors: Immunohistochemical Expression. (March 2015) - Bongiovanni, L.; Romanucci, M.; Malatesta, D.; D'Andrea, A.; Ciccarelli, A.; Della Salda, L.
Survivin is reexpressed in most human breast cancers, where its expression has been associated with tumor aggressiveness, poor prognosis, and poor response to therapy. Survivin expression was evaluated in 41 malignant canine mammary tumors (CMTs) by immunohistochemistry, in relation to histological grade and stage, and correlated with that of some related molecules (β-catenin, caspase 3, heat shock proteins) to understand their possible role in canine mammary tumorigenesis. An increase in nuclear survivin expression, compared with healthy mammary glands, was observed in CMTs, where nuclear immunolabeling was related to the presence of necrosis. No statistically significant relation was found between the expression of the investigated molecules and the histological grade or stage. The present study may suggest an important involvement of survivin in CMT tumorigenesis. Its overexpression in most of the cases evaluated might suggest that targeting survivin in CMTs may be a valid anticancer therapy.